Regulating Aerial Photography and Videography Proportionately: Some Thoughts on the SAL Seminar “Droning on About Journalism – Remotely Piloted Aircraft, Newsgathering, and Law” - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2014)
The concept and practice of aerial photography and videography have been around for some time. But it was only in the last few years that such media production via remote means has achieved mainstream use. The convergence of cutting-edge technological developments in gyroscopic gimbals, far-range wireless transmissions, GPS-enablement in stabilisation, compact devices producing digital image quality and so forth has led to the proliferation of affordable camera-carrying “drones” that even hobbyists can pilot reasonably well with ease. Thus far, there have not been any reports of serious mishaps involving the use of these rotor-propelled copters. However, the controversial appellation inaccurately attached to such tools has generated considerable public concern and even more considerable public misconception, particularly that relating to privacy, safety, and the protection of commercial interests. But lost in the paranoid cacophony is a question that warrants proper thought and analysis: how can the use of such tools be regulated in a way that is proportionate and appreciative of their often unarticulated benefits?